Spreading and proliferation of cultured rat bone marrow stromal cells on the surface of bioactive glass ceramics - Kiroshka, V.V.; Savvova, O.V.; Bozhkova, Yu.O.; Tamarina, I.V.; Fesenko, A.I. (Вiopolymers and Cell, 2017)
Aim. To study spreading profile, cytoskeleton organization and proliferation of bone marrow stromal cells upon cultivation on the glass-crystalline material (GCM) surfaces with different chemical composition and solubility. Methods. GCMs with different CaO: P₂O₅ ratios were used. Actin cytoskeleton in cells was visualized using fluorescent TRITC-conjugated phalloidin. Cell proliferation was studied using MTT test. Results. Cell cultivation on highly soluble B-series GCM (Ca/P=5) led to appearance of fibroblast-like cells; their actin cytoskeleton filaments were uniformly distributed within the cytoplasm. In this case, proliferation dynamics was similar to that under cultivation on plastic. Cultivation on A and C series of GCM with a reduced Ca/P (1.4–2.58) resulted in a decrease of cell spreading and their proliferation index (up to 2–3 times) relative to the control. Conclusions. The material solubility and Ca/P superficial ratio are the main factors, determining cell interaction with GCMs.